Meteorological factors association with under-five children diarrhea incidence in central Gondar zone, Northwest Ethiopia. A time series study - Gelila Yitageasu; Hailemariam Feleke; Zewudu Andualem; Lidetu Demoze; Kidist Asrat; Zemichael Gizaw (BMC Research Notes)
Abstract Background Under 5 children diarrhea has been one of the major public health concerns in countries with limited resources such as Ethiopia. Understanding the association between under-5 diarrhea and meteorological factors will contribute to safeguarding children from adverse health effects through early warning mechanisms. Thus, this study aimed to explore the association between under-5 diarrhea and meteorological factors to reduce health risks. Methods A time-series ecological study was used to explore the association between meteorological factors and under-5 diarrhea incidence. Spearman’s correlation was computed to test the correlation and a negative binomial regression model was fitted to determine the associations of meteorological factors with under-5 diarrhea incidence. The multicollinearity was checked using the variance inflation factor (VIF) before the multivariable regression analysis and the value was 5. aIRRs with 95% CIs and a significance level of 0.05 were used for all the statistical tests. Statistical analyses were conducted using STATA 14.2 software. Results The highest under-5 diarrhea incidence morbidities was 180.9 per 1000 per year for under-five children. This study revealed a positive and negative correlation between the count of under-5 diarrhea and average monthly temperature and rainfall at 0 and 2 lag months with RRs of 1.0209 (95% CI: 1.0034–1.0387), RR 1.0202(95% CI:1.0022–1.0385), RR 0.999(95% CI:0.9985–0.9996), and RR 0.9992(95% CI:0.9987–0.9997) respectively. Conclusion There was an association between under 5 diarrhea incidence and meteorological factors in the Central Gondar Zone. The mean monthly temperature and rainfall were positively and negatively related to the incidence of diarrhea in children under 5 years old. The results showed that the observed association between meteorological factors and under-5 diarrhea incidence could be used as evidence for the use of early warning systems for the prevention of childhood diarrhea.